Metastatic behaviour of giant cell tumour of the spine - Donthineni, Rakesh (Springer-Verlag, 2008)
Lung metastases from giant cell tumours (GCT) of the spine have not been specifically addressed in the literature. We reviewed our cases and compared the incidence, treatment, and outcomes with those from the extremities. Between 1970 and 2006, we identified seven cases (three females and four males) of lung metastases from a total of 51 cases of GCT of the spine (13.7%). Four of the seven patients had presented to our institution with a spine recurrence after previous treatments and the rest developed recurrences later. The treatments for the lung nodules consisted of metastectomy in two and chemotherapy in six patients. At the latest follow-up (ranging from 18 to 126 months), two had died of the disease, two had no evidence of the disease, and three were alive with disease. Our series shows a higher metastatic rate from spine GCT as compared to those from the extremities, but the overall behaviour and treatment outcomes of the lung metastases are similar. When there is a recurrence of GCT, with or without metastases, the local and possibly the metastases should be biopsied to confirm the original diagnosis. Progression of benign GCT into an aggressive sarcoma has been documented, and the method of management should be altered.